Facile synthesis of MnOx nanoparticles sandwiched between nitrogen-doped carbon plates for lithium ion batteries with stable capacity and high-rate capability. Issue 23 (17th February 2016) - Zhou, Xiangyang; Bai, Tao; Chen, Feng; Tang, JingJing; Liao, Qunchao; Zhao, Yingrui; Yang, Juan
Abstract : MnO x nanoparticles sandwiched between nitrogen-doped carbon plates architecture (C/MnO x /C) has been successfully synthesized via a step-by-step strategy. Abstract : In this work, a material consisting of MnO x nanoparticles sandwiched between nitrogen-doped carbon plates (C/MnO x /C) has been successfully synthesized via a step-by-step strategy. It is demonstrated that the MnO x nanoparticles are well sandwiched between the double nitrogen-doped platelike carbon sheets. As an anode material for lithium-ion batteries, the double nitrogen-doped platelike carbon sheets encapsulating MnO x can not only address the issues related to the aggregation and volumetric changes of manganese oxides during the Li + insertion/extraction, but also effectively shorten the transport path of Li + ions and enhance the conductivity. As a result, the prepared C/MnO x /C composite exhibits stable cycling performance and superior high rate capability. The reversible capacity of C/MnO x /C after 100 cycles is as high as 770.9 mA h g −1, which is comparable with the initial capacity at 0.2 A g −1, and even at a high rate at 1 A g −1, it can deliver a high reversible of 443.9 mA h g −1, demonstrating the rational architecture design of the encapsulation of MnO x with nitrogen-doped platelike carbon layers.